Analisis Financial Distress dengan Menggunakan Analisis Survival - Rivanza Dhia Ramadhan; Brady Rikumahu (Syntax Corporation Indonesia, 2024)
Financial Distress refers to a situation in which the financial condition of a company is poor, indicated by insufficient capital and difficulties in meeting financial obligations throughout the maturity of its payments. The underlying causes include low asset value, high corporate debt, and poor corporate performance. Hence, the company must take measures to maintain the financial condition of the company from experiencing financial difficulties. The objective of this study is to clearly understand the influence of liquidity, leverage, profitability, and firm size on financial distress in Sub-Sector Pakaian & Barang Mewah companies listed on the Indonesia Stock Exchange from 2016 to 2022. The data used is secondary data obtained from the annual financial reports of the company. The sample used is obtained via the technique of purposive sampling. Survival analysis is a method used. The hypotheses in this data analysis were tested using SPSS 23. Data analysis shows that Liquidity, Leverage, Profitability, and Company Size simultaneously have a significant impact as the independent variables contribute additional effects to the model, resulting in a good fit for the model. It is known that Leverage and Company Size have a significant influence on Financial Distress when considered individually. Liquidity and Profitability do not have a significant impact on Financial Distress